2018
DOI: 10.3390/su10124336
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assessment Method for Sustainability Implementation in Product Innovation

Abstract: Companies, striving towards an effective and systematic integration of a strategic sustainability perspective in product innovation, need to treat the implementation of necessary processes and tools, as well as their continuous improvement, as a project in itself. An efficient way to measure the current sustainability implementation level in the organization, as well as guidance for progression, is required. To meet this need, a novel self-assessment was developed, which provides companies with a tool to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…The five levels of sustainability compliance (adapted from Willard, 2012, as cited in Schulte and Isaksson Hallstedt, 2018) [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Understanding the Implementation Of Eco‐innovations And Ecodmentioning
confidence: 99%
“…The five levels of sustainability compliance (adapted from Willard, 2012, as cited in Schulte and Isaksson Hallstedt, 2018) [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Understanding the Implementation Of Eco‐innovations And Ecodmentioning
confidence: 99%
“…Application of instruments reducing pollution, alternative energy sources as well as other environmentally friendly instruments is related to the improvement of product technology. When investigating the implementation of product innovations in companies aimed at increasing the sustainability of their actions, some authors encountered the need to improve technology first of all (Schulte and Hallstedt 2018). The aforementioned authors argue that sustainability is enhanced through the use of innovative production methods, tools, processes, and even by changing the approach to the existing operations.…”
Section: Relationship Between Sustainable Technology and Sustainable mentioning
confidence: 99%
“…The aforementioned authors argue that sustainability is enhanced through the use of innovative production methods, tools, processes, and even by changing the approach to the existing operations. Reviewing the possible models of sustainable innovative operations in companies, they eventually arrive at the conclusion that the basis of sustainability is the choice of appropriate advanced technology allowing application of sustainable processes only (Schulte and Hallstedt 2018).…”
Section: Relationship Between Sustainable Technology and Sustainable mentioning
confidence: 99%
“…Application of instruments reducing pollution, alternative energy sources as well as other environmentally friendlyinstruments is related to the improvement of product technology. When investigating the implementation of product innovations in companies aimed at increasing the sustainability of their actions, some authors encountered the need to improve technology first of all[25]. The aforementioned authors argue that sustainability is enhanced through the use of innovative production methods, tools, processes, and even by changing the approach to the existing operations.Reviewing the possible models of sustainable innovative operations in companies, they eventually arrive at the conclusion that the basis of sustainability is the choice of appropriate advanced technology allowing application of sustainable processes only[25].Preconditions for improving sustainable competitive performance in small-and medium-sized enterprises have been examined by Ma Degong et al[26].…”
mentioning
confidence: 99%
“…When investigating the implementation of product innovations in companies aimed at increasing the sustainability of their actions, some authors encountered the need to improve technology first of all[25]. The aforementioned authors argue that sustainability is enhanced through the use of innovative production methods, tools, processes, and even by changing the approach to the existing operations.Reviewing the possible models of sustainable innovative operations in companies, they eventually arrive at the conclusion that the basis of sustainability is the choice of appropriate advanced technology allowing application of sustainable processes only[25].Preconditions for improving sustainable competitive performance in small-and medium-sized enterprises have been examined by Ma Degong et al[26]. Their research has inter alia confirmed that innovative technologies have the greatest impact on competitiveness enhancement processes.Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 4 February 2019 Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: mentioned authors explored the peculiarities of applying internationally recognised, advanced technologies in small-and medium-sized enterprises in emerging economies.…”
mentioning
confidence: 99%